Early Childhood Development (Physical, Intellectual, Emotional, Social, Moral and Religious) and Its Implications toward Early Childhood Education - Oskar, Ruani; Khairunnisa, Fadhillah Izzah; Harto, Kasinyo; Suryana, Ermis (Journal of Social Work and Science Education, 2025)
This study describes early childhood development in Rambutan District, Jalan Lingkar Selatan, Sungai Pinang village and analyze the role of early childhood education (PAUD) in supporting children’s growth and development in various aspects. With a descriptive qualitative approach, data collection was carried out through observation, interviews, and documentation. The results of the study showed that children’s physical, cognitive, social emotional, moral, and religious development differed, depending on the family environment, access to education, and the quality of social interaction. Children involved in the PAUD program with a play-based curriculum showed good development, especially in cognitive and social aspects. In addition, collaboration between PAUD institutions and parents is very important in creating a supportive learning environment. This study suggests the development of a curriculum based on local values, increasing teacher capacity, and utilizing technology to improve the quality of early childhood education in the area.